Multimodal approach to portal hypertension and gastric varices before hepatic resection for hepatocellular carcinoma: a case report - Norifumi Harimoto; Kenichiro Araki; Ryo Muranushi; Kouki Hoshino; Kei Hagiwara; Norihiro Ishii; Mariko Tsukagoshi; Takamichi Igarashi; Akira Watanabe; Norio Kubo; Kei Shibuya; Masaya Miyazaki; et al. (Surgical Case Reports, 2020)
Abstract Background Liver cirrhosis occurs in approximately 80–90% of patients with hepatocellular carcinoma (HCC), and hepatic resection may be dangerous because of well-documented liver cirrhosis, which may be accompanied by portal hypertension (PH). Here we report a patient with advanced HCC with gastric varices and PH who experienced a good clinical course after undergoing balloon-occluded retrograde transvenous obliteration (BRTO), percutaneous transhepatic portal vein embolization (PTPE), hand-assisted laparoscopic (HALS) splenectomy, and right lobectomy of the liver. Case presentation A 72-year-old man had two HCCs with gastric varices. CT revealed one tumor (4.5 cm) located in segment 7, involving the right hepatic vein, adjacent to the middle hepatic vein. Another tumor (2.7 cm) was located in segment 6. He first underwent BRTO for gastric varices and PTPE for planned right lobectomy of the liver. To reduce PH, HALS splenectomy was performed, and uncomplicated right lobectomy of the liver was performed 10 weeks after the first visit. He has remained free of recurrence for at least 1 year. Conclusions Our patient underwent uncomplicated BRTO, PTPE, HALS splenectomy, and right lobectomy of the liver for advanced HCC with PH. Controlling portal pressure is important when hepatic resection is required to treat HCC with PH.